The Conceivable Functions of Protein Ubiquitination and Deubiquitination in Reproduction - Wang, Jiayu; Zhou, Qi; Ding, Jinli; Yin, Tailang; Ye, Peng; Zhang, Yan (Frontiers in Physiology, 2022)
Protein ubiquitination with general existence in virtually all eukaryotic cells serves as a significant post-translational modification of cellular proteins, which leads to the degradation of proteins via the ubiquitin-proteasome system. Deubiquitinating enzymes (DUBs) can reverse the ubiquitination effect by removing the ubiquitin chain from the target protein. Together these two processes participate in regulating protein stability, function, and localization, thus modulating cell cycle, DNA repair, autophagy, and transcription regulation. Accumulating evidence indicates that the ubiquitination/deubiquitination system regulates reproductive processes, including the cell cycle, oocyte maturation, oocyte-sperm binding, and early embryonic development, primarily by regulating protein stability. This review summarizes the extensive research concerning the role of ubiquitin and DUBs in gametogenesis and early embryonic development, which helps us to understand human pregnancy further.